Pengaruh Kotoran Larva Kumbang Tanduk (Oryctes rhinoceros L.) Terhadap Tanah dan Pertumbuhan Bibit Kopi Arabika (Coffea arabika L.) Pada Medium Subsoil Inseptisol - Nermianty Pasaribu; Wardati Wardati; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The aim of this research is to know the influence of giving feces of horned beetle larvae (O. Rhinoceros) towards soil and plants in obtaining exact dose to the growth of Arabica coffee seedling (Coffea Arabica L.). This research  has been conducted in Experimental Station of Agriculture Faculty of Riau University, Campus Bina Widya km 12,5 Simpang Baru Village, Tampan Sub District, Pekanbaru City. This study was conducted from March to July 2017. This study was conducted using a Complete Randomized Design (CRD). The treatment was the feces of horned beetles larvae which consists of six dose levels, such as: K0 : 0 g each plant, K1: 25 g each plant, K2: 50 g each plant, K3: 75 g each plant, K4: 100 g each plant, K5: 125 g each plant. Each treatment was repeated three times to make 18 experimental units. Data obtained from the observations were analyzed using variance analysis (Anova). Diversity results are followed by Duncan multiple range test at 5% level. Observed parameter were seedling height, the increase of stem diameter, the increase of leafs number, leafs area, roots volume, shoot root ratio and seedling dry weight. The results show that feces of horned beetles larvae application can increase the chemical properties of the soil such as N-total, P-total, K-total, C-organic, pH and decrease C/N ratio on subsoil Inceptisol. The application of this fertilizer increases the number of leafs, stem diameter, roots volume, seedling height, leafs area,  and dry weight. Applying 100 g feces of horned beetles larvae have shown good growth for vegetative growth of Arabica coffee seedling on subsoil Inceptisol. Keywords: Arabica coffee seedling, feces of horned beetles larvae, subsoil              Inceptisol